Response to: Health Poverty Alleviation Project in Rural China: Impact on Poverty Vulnerability, Health Status, Healthcare Utilization, Health Expenditures [Letter] - Muttaqin MZ (Dove Medical Press, 2024)
M Zaenul Muttaqin Public Administration Study Program, Cenderawasih University, Jayapura City, IndonesiaCorrespondence: M Zaenul Muttaqin, Email mzaenul69@gmail.com